EVALUATING ANTIBIOTIC STEWARDSHIP PROGRAMS IN PRIMARY CARE THROUGH THE INTEGRATED ROLES OF GENERAL PRACTICE, CLINICAL LABORATORY SCIENCE, PHARMACY, AND SOCIAL WORK - TURKI ABDULLAH ALDALAAN, AHMAD BAQIR ALMUHAIMEED, FAWAZ IBRAHIM ABDULLAH ALSWEED, SAUD ABDULAZIZ AL-OTHMAN, ADNAN ABDULMALIK AL-TALHI, WALID HILAL NAJI AL-SAEDI; AMANI AHMED ALOSAIMAH, REEM KHADER ALANAZI, SUMAYAH OTHMAN ALBALBISI, AHMED ABDULLAH ALMUTAWA, KHALED MOHAMMED B. ALSUFAYAN, MOHAMMED MUSALLAM THAFAR ALDAWSARI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Antimicrobial resistance (AMR) is one of the most significant worldwide health challenges in contemporary reality, and the misuse of antibiotics in the primary care is one of the major reasons. Even though hospitals have been using the Antibiotic Stewardship Programs (ASPs), most of the antibiotic prescriptions are done in the community. To practice good stewardship in the primary care, there must be multidisciplinary collaboration between general practitioners (GPs), clinical laboratory scientists, pharmacists, and social workers. Purpose: The purpose of the review is to assess the practice of antibiotic stewardship programs in primary care using the combined efforts of the general practice, clinical laboratory science, pharmacy, and social work. Methods: PubMed and Google Scholar were used to conduct a narrative synthesis of peer-reviewed literature on the topic published between 2016 and 2024. They included studies on outpatient antibiotic stewardship, diagnostic stewardship, pharmacy-led interventions, and the social determinant of antimicrobial use. Results: It has been seen that primary care ASPs can help decrease inappropriate prescribing, especially with the help of the CDC Core Elements and diagnostic feedback, pharmacist collaboration, and the behavioral interventions. The accuracy of infection management, pharmacists in prescribing, patient education, and social work on the determinants of antibiotic use behavior, cultural, and equity-related are improved with the help of laboratory diagnostics. But there are still loopholes in implementation, infrastructure and interprofessional integration. Conclusion: A collaborative, interdisciplinary ASP model in primary care, which incorporates clinical, along with laboratory, pharmaceutical, and social aspects, can be the most sustainable means of fighting AMR. Collaborative models, diagnostic innovations and social-behavioral interventions should be given priority in future as a way of ensuring effective stewardship.